2014
DOI: 10.1161/strokeaha.114.005663
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Carotid Atherosclerosis on the Risk of Adverse Cardiac Events in Patients With and Without Coronary Disease

Abstract: Consecutive hospitalized and ambulatory patients undergoing nonemergent coronary angiography between January 2007 and May 2009 were enrolled in the Tel-Aviv Prospective Angiography Study, as previously described. 8 Patients undergoing a carotid ultrasoundBackground and Purpose-Carotid atherosclerosis (CA) is reportedly a strong predictor of imminent cardiac events even in the absence of established coronary artery disease (CAD). We examined the differential impact of CA on the risk of major adverse cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 14 publications
1
23
0
1
Order By: Relevance
“…This predictive ability has a wide range of potential applications among both asymptomatic individuals with vasculopathic risk factors and patients with symptoms of arterial diseases. 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…This predictive ability has a wide range of potential applications among both asymptomatic individuals with vasculopathic risk factors and patients with symptoms of arterial diseases. 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…Together with past manifestations of ACS, carotid atherosclerosis is thought to reflect a subsequent worsening of CAD and considered a risk factor for CAD. 5,6,14,15 The grade of CECP could be helpful to predict future CV events, irrespectively of its dot or extensive uptake pattern. 14 A semi-quantitative assessment method can be more accessible than a time-consuming quantitative technique.…”
Section: Prognosis Of Contrast-enhancement Of Carotid Plaque For CLmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the leading cause of death worldwide, including the United States, Europe, and Japan. Previous studies have demonstrated that arteriosclerosis is a key mechanism in the development of CVD, and the degree of arteriosclerosis is a strong surrogate marker for determining the incidence of CVD 1 ) .…”
Section: Introductionmentioning
confidence: 99%